Reconceptualization and Implementation of Syirkah Mudharabah: An Islamic Political Law Analysis - Muhsin Hariyanto; Zuly Qodir (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
This article seeks to elucidate the fundamental concept of shirkah muḍārabah (business partnership based on sharing agreement) within both classical and contemporary Islamic legal literature, as well as its historical application in Islamic contexts. It endeavors to reconceptualize this notion and its implementation, particularly within the Indonesian framework, through the lens of Islamic law.  Through library research and critical reconstructive analysis, it is concluded that the concept of shirkah muḍārabah can be effectively implemented, largely devoid of socio-economic and political constraints, particularly in partnership-based business activities between investors-capitalists and proprietors who are committed to conducting business partnerships grounded in trust, founded on the principles of honesty, transparency, and maqāṣid sharīa (higher objectives of Islamic jurisprudence) argument.